Doxycycline Changes the Transcriptome Profile of mIMCD3 Renal Epithelial Cells - Jung, Hyun Jun; Coleman, Richard; Woodward, Owen M.; Welling, Paul A. (Frontiers in Physiology, 2021)
Tetracycline-inducible gene expression systems have been used successfully to study gene function in vivo and in vitro renal epithelial models but the effects of the common inducing agent, doxycycline (DOX), on gene expression are not well appreciated. Here, we evaluated the DOX effects on the transcriptome of a widely-used renal epithelial cell model, mIMCD3 cells, to establish a reference. Cells were grown on permeable filter supports in the absence and presence of DOX (3 or 6 days), and genome-wide transcription profiles were assessed using RNA-Seq. We found DOX significantly altered the transcription profile, changing the abundance of 1549 transcripts at 3 days and 2643 transcripts at 6 days. Within 3 days of treatment, DOX significantly decreased the expression of multiple signaling pathways (ERK, cAMP and Notch) that are associated with cell proliferation and differentiation. Genes associated with cell cycle progression were subsequently downregulated in cells treated with DOX for 6 days, as were genes involved in cellular immune response processes and several cytokines and chemokines, correlating with a remarkable repression of genes encoding cell proliferation markers. The results provide new insight into responses of renal epithelial cells to DOX and a establish a resource for DOX-mediated gene expression systems.